Survival Analysis of COPD Patients in a 13-Year Nationwide Cohort Study of the Brazilian National Health System - Gargano, Ludmila Peres; Zuppo, Isabella de Figueiredo; Nascimento, Mariana Martins Gonzaga do; Augusto, Valéria Maria; Godman, Brian; Costa, Juliana de Oliveira; Acúrcio, Francisco Assis; Álvares-Teodoro, Juliana; Guerra, Augusto Afonso (Frontiers in Big Data, 2022)
Background: Chronic obstructive pulmonary disease (COPD) has large socioeconomical impacts in low- and middle-income countries, but most epidemiological data originate from high-income countries. For this reason, it is especially important to understand survival and factors associated to survival in COPD patients. Objective: To assess survival of COPD patients in Brazil, to identify risk factors associated with overall survival, including treatment options funded by the Brazilian National Health System (SUS). Methodology: We built a retrospective cohort study of patients dispensed COPD treatment in SUS, from 2003 to 2015 using a National Database created from the record linkage of administrative databases. We further matched patients 1:1 based on sex, age and year of entry to assess the effect of the medicines on patient survival. We used the Kaplan-Meier method to estimate overall survival of patients, and Cox's model of proportional risks to assess risk factors. Result: 37,938 patients were included. Patient’s survival rates at 1 and 10 years were 97.6% (CI 95% 97.4 - 97.8) and 83.1% (CI 95% 81.9 - 84.3), respectively. The multivariate analysis showed that male patients, over 65 years old and underweight had an increased risk of death. Therapeutic regimens containing a bronchodilator in a free dose along with a fixed-dose combination of corticosteroid and bronchodilator seem to be a protective factor when compared to other regimens. Conclusion: Our findings contribute to the knowledge of COPD patients' profile, survival rate and related risk factors, providing new evidence that supports the debate about pharmacological therapy and healthcare of these patients.